2023
DOI: 10.1097/aud.0000000000001423
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tonotopic and Default Frequency Fitting for Speech Understanding in Noise in New Cochlear Implantees: A Prospective, Randomized, Double-Blind, Cross-Over Study

Gwenaelle Creff,
Cassandre Lambert,
Paul Coudert
et al.

Abstract: Objectives: While cochlear implants (CIs) have provided benefits for speech recognition in quiet for subjects with severe-to-profound hearing loss, speech recognition in noise remains challenging. A body of evidence suggests that reducing frequency-to-place mismatch may positively affect speech perception. Thus, a fitting method based on a tonotopic map may improve speech perception results in quiet and noise. The aim of our study was to assess the impact of a tonotopic map on speech perception in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 115 publications
2
3
0
Order By: Relevance
“…Coincidentally, Creff et al, 2024 showed speech understanding benefit when using non-standard vs conventional frequency maps aimed at reducing frequency mismatch that appear to closely match the level-corrected tonotopic reference of the present study (i.e., BF70). Tonotopic fitting was achieved via postoperative flat-panel CT for each subject by measuring the cochlear duct length from the round window to a given electrode and then using Greenwood’s (1990) human coefficients to determine the associated frequency.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Coincidentally, Creff et al, 2024 showed speech understanding benefit when using non-standard vs conventional frequency maps aimed at reducing frequency mismatch that appear to closely match the level-corrected tonotopic reference of the present study (i.e., BF70). Tonotopic fitting was achieved via postoperative flat-panel CT for each subject by measuring the cochlear duct length from the round window to a given electrode and then using Greenwood’s (1990) human coefficients to determine the associated frequency.…”
Section: Discussionsupporting
confidence: 67%
“…Coincidentally, Creff et al, 2024 showed speech understanding benefit when using nonstandard vs conventional frequency maps aimed at reducing frequency mismatch that appear to closely match the level-corrected tonotopic reference of the present study (i.e., BF70).…”
Section: Implications For Cochlear Implantssupporting
confidence: 67%
See 3 more Smart Citations